Accidental breaches of the doping regulations in sport: is there a need to improve the education of sportspeople?. Issue 8 (25th July 2005) - Somerville, S J; Lewis, M
Abstract : Objectives: To identify educational needs of elite sportspeople with respect to the doping laws. Methods: A questionnaire survey of 196 Olympic level sportspeople from the fields of athletics, cycling, rowing, and sailing. The questionnaire addressed the date and source of the last doping educational update, the usefulness of current resources, sources of help, and possible ways of improving the system. The questionnaire also sought to estimate the use of nutritional supplements in these sports. Results: Seventy four (38%) athletes responded to the questionnaire. Over 90% of responders had received a doping educational update in the last six months, and most agreed with the statement "I have received the information I need to avoid getting into trouble with the doping laws". Despite this, more than half of responders agreed with the statements "I should receive reminders more often" and "The authorities should do more to educate sportspeople". In addition, there were four people who admitted taking a banned substance by accident. Forty one (55%) reported taking supplements. The team doctor was the most popular source if information on a substance or product was required, with 62% and 66% of subjects stating that they would contact their team doctor when based in the United Kingdom and abroad respectively. The UK Sports website was often suggested in relation to ways of improving knowledge. Conclusions: There is a need to alter the educational process, particularly with respect to contingency planning for minor illness. The use of internet based resources for up to date information about banned substances needs to be promoted, and access to the internet improved. The educational needs of team doctors with respect to the doping laws need to be assessed.